Educação não-formal : a contribuição da música para a educação da sensibilidade na adultez - Balbinot, Gustavo (2013)
The main objective of this research was to verify how Music contributes to the Sensitivity Education in Adulthood. It featured the participation of fifty-five elementary and middle school educators, as adults in a constant personal development and maturing process, of the Municipal Educational System of the city of Nova Prata, located in the countryside of the State of Rio Grande do Sul. The qualitative field research featured a workshop divided into three stages: Pre-Workshop, Music Workshop and Post-Workshop. The questions prepared for each moment of the workshop were answered by the educators in a diary, in which each one of them was able to keep their records. The theoretical framework was developed based on the following concepts: non-formal education, sensitivity, music and adult life. Based on the records in the diaries, it was possible to collect data that proved the importance of Music in sensitivity education. The main objective of this research was to verify how Music contributes to the Sensitivity Education in Adulthood. It featured the participation of fifty-five elementary and middle school educators, as adults in a constant personal development and maturing process, of the Municipal Educational System of the city of Nova Prata, located in the countryside of the State of Rio Grande do Sul. The qualitative field research featured a workshop divided into three stages: Pre-Workshop, Music Workshop and Post-Workshop. The questions prepared for each moment of the workshop were answered by the educators in a diary, in which each one of them was able to keep their records. The theoretical framework was developed based on the following concepts: non-formal education, sensitivity, music and adult life. Based on the records in the diaries, it was possible to collect data that proved the importance of Music in sensitivity education